TOXICITY STUDIES OF A DEVELOPED NEPHROPROTECTIVE POLYHERBAL FORMULATION IN EXPERIMENTAL RATS - SASIKALA S; KANNIKAPARAMESWARI N (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: In the present study, acute toxicity studies were evaluated on scientifically developed nephroprotective polyherbal formulation. Polyherbal formulation consists of ethanolic extracts of dried plants of Boerhavia diffusa (BD) and Achyranthes aspera (AA). Materials and Methods: In an acute toxicity study, polyherbal formulation was administered once orally at doses ranging from 250 mg/kg to 2000 mg/kg for 15 days. Body weight and food consumption were noted during the study period. Behavioral pattern and toxic effects were monitored in each group of animals daily. At the end of the study, blood was withdrawn for hematology and biochemical estimations. The animals were then sacrificed, and the liver, kidney, heart, and brain were dissected out which were observed for any gross morphological changes. The weights of organs were also noted. Results: The results showed no changes in body weight, organ weight, food intake, hematological parameters, and liver function test when compared with control. The organs did not show any evidence of gross morphological changes. Conclusion: It is concluded that developed polyherbal formulation, at a dose of 2000 mg/kg, is safe for long-term treatment of kidney disorders